A simple, hand-held decision support designed tool to help resource-poor farmers improve potato late blight management - Pérez, W.; Arias, R.; Taipe, A.; Ortíz, O.; Forbes, G.; Andrade-Piedra, J.L.; Kromann, P. (Elsevier, 2020)
Many decision support systems (DSS) have been developed to manage potato late blight caused by Phytophthora infestans, but most of these require sophisticated equipment and are not realistic alternatives for small-scale farmers in low-income countries. This research evaluates a simple, hand-held decision support tool (HH-DST) consisting of a disk with three concentric circles, two of which represent factors that drive late blight epidemics and the third providing a spray recommendation. Three disks of different colors have been designed for potato varieties of varying levels of host resistance. The HH-DST was compared with locally used fungicide spray regimes in three trials in Peru, and in six trials in Ecuador, where the tool had been slightly modified. In two additional trials in Peru, the HH-DST was compared with local practices, calendar spraying and two other DSS. The HH-DST and local spray regimes both gave relatively good disease control in all cases, however, the HH-DST was more effective with highly susceptible cultivars both in Ecuador and Peru. The HH-DST also had equal or lower number of sprays per season and had a lower environmental impact, based on the environmental impact quotient (EIQ), than did the local practices. Results were similar in trials comparing different DSS, where all approaches, including the HH-DST, adequately controlled disease, and the HH-DST was among the lowest for both number of sprays per season and environmental impact. The HH-DST is a simple tool that can help resource-poor farmers improve management of potato late blight.